2022
DOI: 10.1038/s41598-022-17989-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and risk of hypertensive disorders of pregnancy

Abstract: Hypertensive disorders of pregnancy (HDP) result in maternal morbidity and mortality but are rarely examined in perinatal studies of sexually transmitted infections. We examined associations between common sexually transmitted infections and HDP among 38,026 singleton pregnancies. Log-binomial regression calculated relative risk (RRs) and 95% confidence intervals (CIs) for associations with gestational hypertension, preeclampsia with severe features, mild preeclampsia, and superimposed preeclampsia. All models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
3
0
1
Order By: Relevance
“…In our study, we were unable to distinguish the use of vaginal versus urine for STI diagnosis. It is possible that our study underestimated rates of gonorrhea, but prevalence is consistent with national data in similar populations [ 12 , 15 ]. We were unable to find detailed data on treatments, adherence, partner treatment, and recurrence of infection.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In our study, we were unable to distinguish the use of vaginal versus urine for STI diagnosis. It is possible that our study underestimated rates of gonorrhea, but prevalence is consistent with national data in similar populations [ 12 , 15 ]. We were unable to find detailed data on treatments, adherence, partner treatment, and recurrence of infection.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, 15% of individuals who tested positive for gonorrhea had a preterm delivery. Our study, in addition to recent work by others, has shown a potential link between gonorrhea and HDP as well as preterm birth [ 14 , 15 , 38 ], within populations that are presumed treated after screening. It may be time for a fresh examination of the impact of STIs on pregnancy health and a new focus on alternative prevention strategies.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations